2017
DOI: 10.1590/1809-4392201602132
|View full text |Cite
|
Sign up to set email alerts
|

Differencial efficiency of two sampling methods in capturing non-volant small mammals in an area in eastern Amazonia

Abstract: This study was the first to evaluate the efficiency of trapping methods in the study of small mammals in the Carajás National Forest, southeastern Brazilian Amazon. It is an area with a unique vegetation type (metalofilic savannah or Canga). The aims of this study were to compare the efficiency of two trapping methods (i.e. live-traps and pitfalls), the bait types used, and evaluate if trapping success varied seasonally. We used four sampling grids, each with six parallel transects. The trap effort for live-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…In fact, PTs provided a higher number of individuals and species not only for didelphids but also for some small cricetids (e.g., Microakodontomys, Oligoryzomys, and Calomys) in comparison with LTs, including species exclusively recorded using this method (M. kunsi, three Cryptonanus species, Pseudoryzomys simplex, and Cavia aperea; see also Cáceres et al, 2011b;Ribeiro-Júnior et al, 2011). These results evidence that sampling methodology can also compromise the diversity patterns uncovered for small mammals as a substantial portion of individuals, and species, are exclusively caught by either live or PTs (e.g., Umetsu et al, 2006;Ardente et al, 2017;Bovendorp et al, 2017).…”
Section: Discussion Species Richness and Diversity Across Scalesmentioning
confidence: 78%
“…In fact, PTs provided a higher number of individuals and species not only for didelphids but also for some small cricetids (e.g., Microakodontomys, Oligoryzomys, and Calomys) in comparison with LTs, including species exclusively recorded using this method (M. kunsi, three Cryptonanus species, Pseudoryzomys simplex, and Cavia aperea; see also Cáceres et al, 2011b;Ribeiro-Júnior et al, 2011). These results evidence that sampling methodology can also compromise the diversity patterns uncovered for small mammals as a substantial portion of individuals, and species, are exclusively caught by either live or PTs (e.g., Umetsu et al, 2006;Ardente et al, 2017;Bovendorp et al, 2017).…”
Section: Discussion Species Richness and Diversity Across Scalesmentioning
confidence: 78%
“…Our results confirm that a combination of methods is required to detect a large proportion of the entire mammal community in Neotropical rainforests. For small mammals multiple trap types and placement options give the best results (Voss and Emmons 1996, Hice and Velazco 2012, dos Santos et al 2015, Lim and Pacheco 2016, Ardente et al 2017) and several studies showed that the addition of pitfall traps led to greatly increased estimates of species richness and abundance of Neotropical small mammals (Hice and Velazco 2013, Bovendorp et al 2017). Pitfall traps typically capture species thought to be rare or within different subsets of the small mammal community, especially terrestrial marsupials of the genus Monodelphis and semiaquatic rodents like the genus Neusticomys (Umetsu et al 2006, Hice and Velazco 2012, dos Santos et al 2015, Palmeirim et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 64 Tomahawk live traps (5.5×6.5×16 cm) were systematically placed in an 8×8 grid at 20 m intervals, and ripe bananas and palm oil as bait were used (Ardente et al 2017;Francis 2019). Trap cages were opened for 3 consecutive months per season, or 1 session, in each study period covering a total study period of 1 year, amounting to 32,555 trap-nights in total.…”
Section: Data Collectionmentioning
confidence: 99%